Analisis Kepatuhan Pekerja dalam Penggunaan Alat Pelindung Diri (APD) Cleaning Service - Amilah Eka Putri; Nurul Pratiwi Army; Rifka Haristantia; Nur Azizah Azzahra; Andi Ferina Herbourina Bonita (Yayasan Literasi Sains Indonesia, 2025)
Cleaning service workers have a high risk of work accidents and exposure to hazardous materials, so the use of Personal Protective Equipment (PPE) is crucial. However, compliance with the use of PPE is still a challenge, especially in the informal sector and outsourcing companies that do not have an adequate K3 system. Objective: This study aims to analyze the level of compliance with the use of PPE in cleaning service workers and identify the factors that affect it. Methods: This study used a qualitative approach with a case study design. Data was collected through semi-structured interviews and direct observation of 15 cleaning service workers working at an outsourcing company in the office sector in North Kolaka Regency in January – March 2025. The data analysis technique is carried out thematically through data reduction, data presentation and conclusion drawn. Results: Results show that the majority of workers understand the importance of PPE and show a fairly high level of compliance. The main driving factors are awareness of personal safety and supervisory supervision, while inhibiting factors include PPE inconvenience, limited tools and lack of supervision. The most commonly used types of PPE are masks, gloves and safety shoes. Conclusion: Adherence to PPE use is influenced by individual, organizational and environmental factors. The company's active role is needed in providing appropriate PPE, supervising and forming a safety-oriented work culture. This research contributes to strengthening K3 policies in the informal sector.